Using a Simulation to Teach Reading Assessment to Preservice Teachers. (31st January 2017) - Ferguson, Kristen
Abstract: Simulations are an underpinning pedagogy and tradition in some professional fields, such as medicine, yet are seldom used in education. In this study, the author reports on the findings of a reading assessment situation activity that she did with preservice early grade (kindergarten to grade 6) teachers. In addition to giving preservice teachers practice conducting reading assessments, this simulation activity also allowed students the opportunity to reflect on teaching strategies (both how they themselves teach while on practicum and what they personally experience in their teacher preparation program). Results from questionnaires completed by the participants in the simulation indicate that the simulation was very valuable and expanded the preservice teachers' perspectives on reading, assessment practices, and how they view students. There is very little published about simulations in education, particularly in literacy education, and this study adds an important perspective on using simulations in preservice classrooms and for professional development for practicing teachers.